Marketing and sponsorship in French football league. (23rd May 2011) - Teixeira, Mário; Correia, Abel
This paper seeks to analyse the production function of the French league, using a quantile regression in order to be able to extend the study along the whole production distribution aiming to investigate whether the relationship between production and financial and marketing variables is homogenous and stable through the distribution by running regressions for average total wins. Policy implications are derived.